Strategi Komunikasi Pemasaran Digital untuk Meningkatkan Brand Awareness Melalui Media Sosial Instagram Bimbapedia - Ade Budi Santoso; Saiful Romadon; Jatayu Hadi Prakoso (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Bimbapedia is (Indonesian Children's Education Tutoring), which aims to make Bimba Partners (entrepreneurs) confident when opening a business with a Premium design appearance, such as Roll Banners, Banners, Brochures, Uniforms and several Marketing Tools that have Brand Value. The purpose of this study is to find out and examine How the Bimbapedia Indonesia Content Concept increases Brand Awareness and examines the Engagement Rate through Instagram Media @bimbapedia to increase Brand Awareness of Users, Followers or mira bimbapedia. This study uses the theory of digital revolution, New Wave Marketing and Engagement Rate analysis. The results of this study are how Creative Content can increase Brand Awareness through Kudo's Instagram social media, how through Content Kudo tries to attract Awareness with its consumers, this is in accordance with the concept of Content Marketing where the relationship between a Brand and its consumers is Horizontal. In increasing Brand Awareness through content on Instagram social media, Kudo uses elements contained in the New Content Marketing concept 7 (Seven) steps of Content Marketing, namely: determining goals, mapping targets, determining the main theme of the Content presented, determining when and who creates Content, distributing Content, strengthening Content and evaluation. The Kudo Brand already has a strong character in online business activists because the Kudo Brand has 7 steps of Content Marketing.